Development and validation of 3‐CpG methylation prognostic signature based on different survival indicators for colorectal cancer. Issue 6 (7th April 2021) - Huang, Hao; Zhang, Lei; Fu, Jinming; Tian, Tian; Liu, Xinyan; Liu, Yupeng; Sun, Hongru; Li, Dapeng; Zhu, Lin; Xu, Jing; Zheng, Ting; Jia, Chenyang; et al.
Abstract: Abnormal DNA methylation is considered a vital hallmark to regulate gene expression and influence the development and progression of colorectal cancer (CRC). Although CRC‐related methylation prognostic models have been developed, their clinical application is limited due to the lack of external validation and extension to other survival evaluation indicators. Therefore, this study aimed to develop and validate novel methylation prognostic models correlated with different survival indicators for individualized prognosis prediction for CRC patients. The prognostic‐related CpG sites of methylation‐driven genes screened by the MethylMix algorithm were identified and validated in The Cancer Genome Atlas (TCGA) CRC methylation data and our methylation data. The prognostic models correlated with different survival evaluation indicators (overall survival [OS] and disease‐free survival [DFS]) were developed and validated in the TCGA CRC dataset ( N  = 376) and our independent CRC dataset ( N  = 227). We utilized the combination of selected 3‐CpG methylation sites in three genes ( DAPP1, FAM3D, and PIGR ) to construct a prognostic risk‐score model. In the training dataset, Kaplan–Meier survival analysis demonstrated that high‐risk patients had significantly poorer survival than low‐risk patients ( p OS  = .0014; p DFS  < .001). Then, the 3‐CpG methylation signature was successfully validated as an independent predictor in the testing data set ( p OS  = .016; p DFS  = .016). A prognostic nomogram was constructed and validated. Additionally, mediation analysis revealed the direct effect of the methylation signature on CRC prognosis ( p OS  = 9.149e−06; p DFS  = .001). In summary, our study revealed that the 3‐CpG methylation signature might be a potential prognostic indicator to facilitate individualized survival prediction for CRC patients.